Individual-, home- and preschool-level correlates of preschool children's sedentary time - Suvi Määttä; Hanna Konttinen; Rejane Augusta de Oliveira Figueiredo; Ari Haukkala; Nina Sajaniemi; Maijaliisa Erkkola; Eva Roos (BMC, 2020)
Abstract Background Prechoolers' significant portions of sedentary time (ST) is a public-health concern due to its high prevalence and negative health consequences. However, few studies have explored correlates of preschoolers' ST covering individual-, home- and preschool- factors within one study. The aim of this study was to identify the associations between multiple individual-, home- and preschool-level factors and preschoolers' ST. In addition, it was studied how much individual-, home- and preschool-level factors explained the variance in children's ST. Methods A total of 864 children aged three to six, their parents and 66 preschools participated in the cross-sectional DAGIS study, which occurred between 2015 and 2016. The children wore an accelerometer for 1 week. Guardians, principals and early educators completed questionnaires covering the potential correlates of children's ST, for example, temperament, practices, self-efficacy and regulations. Multilevel regression analyses were conducted in multiple steps; calculation of marginal and conditional R2 values occurred in the final phase. Results Of the 29 studied correlates, the following factors remained significant in the final models. Being a boy (p < 0.001) and having high levels of surgency temperament (p < 0.001) were associated with lower ST. Regarding the home setting, frequent co-visits in physical activity (PA) places (p = 0.014) were associated with lower ST. Higher parental perceived barriers related to children's outside PA (p = 0.032) was associated with higher ST. None of the preschool setting factors remained significant in the final model. Approximately 11% of the variance in children's ST was attributed to factors related to the individual level whereas 5% was attributed to home-level factors; and 2% to preschool-level factors. Conclusions This study identified a set of correlates of preschool children's ST. Interventions aimed at reducing children's ST should develop strategies targeting established correlates of preschoolers' ST covering individual-, home- and preschool-level factors. The preschool-level factors included in this study explained little the variance in children's ST. However, the included measures may not have captured the essential preschool-level factors that specifically influence children's ST. Therefore, more studies are needed regarding potential preschool-level factors.